Reduction of Energy Consumption of Brackish Water Reverse Osmosis Desalination System Via Model Based Optimisation - Mudhar A. Al-Obaidi; Alanood A. Alsarayreh; I. M. Mujtaba (Journal of Techniques)
Reverse Osmosis (RO) process is being engaged to yield fresh water from brackish water sources. However, the RO process is characterized by its high specific energy consumption (SEC) owing to high-pressure pumps. The current study focuses on reducing the SEC of the brackish water RO desalination plant using model-based optimization practice. The inlet conditions of RO process such as the feed pressure, flow rate (individual membrane module and total plant) and temperature, have a substantial influence on the performance indicators namely, water productivity, product concentration and SEC. Therefore, the optimisation of this study has been directed to determine optimal inlet conditions within feasible limits to minimise SEC. Arab Potash Company (APC) brackish water RO desalination plant has been considered as the case study. The optimal inlet conditions have resulted in a significant energy saving of 27.97% depending on the set of decision variables being considered at a fixed brackish water feed concentration.